Effect of fiber-reinforcement on the fracture resistance in large cavities - Ortiz Magdaleno , Marine (2024)
Extensive cavities with a mesio-occluso-distal preparation (MOD) should be reinforced to distribute the stress caused by occlusal forces to reduce the risk of cuspid and vertical fractures that compromise the success of the restoration. Restorative materials must support masticatory loads; therefore, it is necessary that they provide adequate fracture resistance to avoid restoration failure. The objective of this study was to conduct a review of the scientific literature on the use of polyethylene fibers as reinforcement in MOD cavities. A literature search was conducted using PubMed and Cochrane with the descriptors: "fiber reinforced composite", " polyethylene fibers " and "ribbond fiber" from 2014 to 2024. Currently, the use of polyethylene reinforcement fibers in restorative dentistry has increased, because it has been shown that their mechanical behavior favors fracture resistance by placing them in different orientations on the floor of extensive MOD cavities with 5 mm or more deep, in addition to prevent the appearance and propagation of cracks in areas susceptible to high occlusal forces. The failure mode in teeth restored with polyethylene fibers is usually at the enamel and dentin level, therefore, the placement of reinforcement fibers benefits the fracture pattern.